A comprehensive programme addressing HIV/AIDS and gender based violence - Madri Jansen van Rensburg (Taylor & Francis Group, 2007)
A survey was administered to 304 respondents participating from three areas near Welkom, South Africa. Face-toface interviews were conducted with women from randomly selected households to evaluate the impact of a service provision programme targeting women living with HIV/AIDS and gender based violence. Gender based violence (GBV) awareness and knowledge was high. Respondents had high perceived levels of risk. They reported making various behavioural changes to avoid GBV. The respondents were aware of their legal rights pertaining to GBV. HIV/AIDS knowledge levels and attitudes were acceptable. Behavioural changes included condom use, abstinence and being faithful to one partner. Disclosure of HIV was lower than disclosure of GBV.Awareness and knowledge of female condoms were high, yet usage low. Participants reported that they would be able to introduce condoms to a relationship and negotiate usage with relative ease. Perceived levels of GBV and HIV were high, and stigma levels towards the affected women were also relatively high. The awareness and knowledge levels of GBV and HIV of older respondents were lower than younger respondents. The key findings of this study support the notion of using a holistic approach, targeting more than one issue. There is lower stigma levels associated with combined conditions, which might allow easier access to vulnerable groups. Coordination and collaboration of services are however needed to enable this benefit.